The impact of clinical heterogeneity on conducting network meta-analyses in transthyretin amyloidosis with polyneuropathy. (3rd May 2020) - Samjoo, Imtiaz A.; Salvo, Elizabeth M.; Tran, Diana; Amass, Leslie; Stewart, Michelle; Cameron, Chris
Abstract: Objective: The comparative safety and efficacy of tafamidis, patisiran and inotersen treatments for transthyretin amyloidosis with polyneuropathy (ATTR-PN) has not been evaluated in clinical trials. In the absence of head-to-head evidence, indirect treatment comparisons such as network meta-analyses (NMAs) can be performed to evaluate relative effects of treatments. This study aims to assess the feasibility of conducting an NMA of available therapies for ATTR-PN patients. Methods: Pivotal trials for three approved ATTR-PN treatments, tafamidis (Fx-005), patisiran (APOLLO) and inotersen (NEURO-TTR), were compared in terms of study design, baseline population characteristics, outcome definitions and baseline risk. These assessments of heterogeneity informed the decision to perform Bayesian NMAs. Results: Despite similar study designs, clear differences in eligibility criteria between trials were accompanied by imbalances in baseline population characteristics considered to be plausible effect modifiers, such as disease stage and previous treatment. Of the outcomes assessed, only quality of life and adverse events were similarly reported in all trials. Neuropathy outcomes were not evaluated consistently between trials. Conclusions: An NMA of ATTR-PN treatments was not feasible, given the observed cross-trial heterogeneity. This decision highlights the importance of careful consideration for clinical heterogeneity that may threaten the validity of indirect comparisons.